Mathematical Modeling in the Training Process of Secondary Mathematics Teachers - Chavarría-Vásquez, Jesennia; Gamboa-Araya, Ronny (Revista Electrónica Educare, 2024)
Introduction. This article discusses aspects related to mathematical modeling and mathematical modeling as activities that should be included in teacher training processes. The purpose is to cultivate skills in future teachers to integrate mathematical modeling and modeling in the teaching and learning process. Purpose. This paper aims to provide arguments supporting the need for institutions in charge of teacher training to incorporate these processes into their curricular structures. It also aims to furnish ideas about some types of activities that the teacher can implement in class. Discussion. The ideas developed here have been built from a literature review related to the subject, as well as from a research process by the authors in 2021. The latter entailed extracting evidence from the proposal to incorporate mathematical modeling into the study curricula of public universities in Costa Rica. This analysis aimed to ascertain whether each course in the description, objectives, contents, and specific indications, among others, made reference to mathematical modeling and if methodological recommendations were provided for its implementation. It is clear that mathematical modeling, as a didactic strategy, holds significant importance in teaching the discipline. Incorporating mathematical modeling processes in the professional training of teachers and academic training of students is relevant for developing specific skills. Conclusions. There is a need to execute actions aimed at teacher training to implement this type of task. The objective is that students recognize the applicability of the subject and that the knowledge of it enables them to understand its context.